Global and regional burdens of oral cancer from 1990 to 2017: Results from the global burden of disease study. Issue 2 (18th February 2020) - Ren, Zhen‐Hu; Hu, Chuan‐Yu; He, Hai‐Rong; Li, Yuan‐Jie; Lyu, Jun
Abstract: Background: Data on the incidence, mortality, and other burden of oral cancer as well as their secular trends are necessary to provide policy‐makers with the information needed to allocate resources appropriately. The purpose of this study was to use the Global Burden of Disease (GBD) 2017 results to estimate the incidence, mortality, and disability‐adjusted life years (DALYs) for oral cancer from 1990 to 2017. Methods: We collected detailed data on oral cancer from 1990 to 2017 from the GBD 2017. The global incidence, mortality, and DALYs attributable to oral cancer as well as the corresponding age‐standardized rates (ASRs) were calculated. The estimated annual percentage changes in the ASRs of incidence (ASRI) and mortality (ASRM) and age‐standardized DALYs of oral cancer were also calculated according to regions and countries to quantify the secular trends in these rates. Results: We tracked the incidence, mortality, and DALYs of oral cancer in 195 countries/territories over 28 years. Globally, the incidence, mortality, and DALYs of oral cancer increased by about 1.0‐fold from 1990 to 2017. The ASRI of oral cancer showed a similar trend, increasing from 4.41 to 4.84 per 100, 000 person‐years during the study period. The ASRM remained approximately stable at about 2.4 per 100, 000 from 1990 to 2017, as did the age‐standardized DALYs, at about 64.0 per 100, 000 person‐years. ASRI was highest in Pakistan (27.03/100, 000, 95% CI = 22.13‐32.75/100, 000), followed by Taiwan China, and lowest in Iraq (0.96/100, 000, 95% CI = 0.86‐1.06/100, 000). ASRM was highest in Pakistan (16.85/100, 000, 95% CI = 13.92‐20.17/100, 000) and lowest in Kuwait (0.51/100, 000, 95% CI = 0.45‐0.58/100, 000). Conclusions: The ASRI of oral cancer has increased slightly worldwide, while the ASRM and age‐standardized DALY have remained stable. However, these characteristics vary between countries, suggesting that current prevention strategies should be reoriented, and much more targeted and specific strategies should be established in some countries to forestall the increase in oral cancer.